2015
DOI: 10.1016/j.yrtph.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment for ethanol-based topical antiseptic use by health care workers: Evaluation of developmental toxicity potential

Abstract: Ethanol-based topical antiseptic hand rubs, commonly referred to as alcohol-based hand sanitizers (ABHS), are routinely used as the standard of care to reduce the presence of viable bacteria on the skin and are an important element of infection control procedures in the healthcare industry. There are no reported indications of safety concerns associated with the use of these products in the workplace. However, the prevalence of such alcohol-based products in healthcare facilities and safety questions raised by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 100 publications
1
46
0
Order By: Relevance
“…These results indicate that sanitizer solution has suitable compatibility with hand skin, which is consistent with the findings of Zaragoza et al, where the skin condition and tolerability improved by using alcoholic products (19), this result was consistent with the outcomes of Elaine et al They found that skin disorders were less in alcoholic solutions with emollient (20). Also, the results of Maier et al demonstrated that frequent use of alcoholic solutions for hygiene is not a danger for people and it can be one of the best ways to prevent infection (21).…”
Section: Discussionsupporting
confidence: 87%
“…These results indicate that sanitizer solution has suitable compatibility with hand skin, which is consistent with the findings of Zaragoza et al, where the skin condition and tolerability improved by using alcoholic products (19), this result was consistent with the outcomes of Elaine et al They found that skin disorders were less in alcoholic solutions with emollient (20). Also, the results of Maier et al demonstrated that frequent use of alcoholic solutions for hygiene is not a danger for people and it can be one of the best ways to prevent infection (21).…”
Section: Discussionsupporting
confidence: 87%
“…48,49 Recent assessments of the exposure of healthcare personnel to alcohol-based hand rubs concluded that such products are safe when used as intended. 49,50 Despite the frequent exposure of healthcare personnel to alcohol-based disinfectants, 48 these products appear to pose little risk to healthcare personnel if used as directed. For example, a review of data from 69,075 full-time work years by healthcare personnel revealed that reported injuries or illnesses due to germicides, including alcohol, were very uncommon.…”
Section: Safetymentioning
confidence: 99%
“…A review study (Lachenmeier’s ( 2008 )) concluded that ethanol absorption through the wounds via pharmaceutical preparations is not toxic to adults. Furthermore, it was found in another study that a high-frequency use and exposure to alcohol-based hand sanitizers or surgical scrubs for hand and skin hygiene do not cause significant risks of toxicity (Maier et al 2015 ). In addition, amounts of residual solvent in electrospun meshes would be lower than in most ethanol-based products in both of the studies described above.…”
Section: Discussionmentioning
confidence: 99%